The murder of a moderate : political biography of Appapillai Amirthalingam - Sabaratnam, T. (Dehivala : Nivetha Publishers, 1996)
Biography of A. Amirtaliṅkam, b. 1927, politician from Sri Lanka.
Keywords: Politicians -- Sri Lanka -- Biography; Sri Lanka -- Politics and government